How I treat thrombotic thrombocytopenic purpura and atypical haemolytic uraemic syndrome. (6th January 2014) - Scully, Marie; Goodship, Tim
Summary Thrombotic thrombocytopenic purpura (TTP) and atypical haemolytic uraemic syndrome (aHUS) are acute, rare life‐threatening thrombotic microangiopathies that require rapid diagnosis and treatment. They are defined by microangiopathic haemolytic anaemia and thrombocytopenia, with renal involvement primarily in aHUS and neurological and cardiological sequelae in TTP. Prompt treatment for most cases of both conditions is with plasma exchange initially and monoclonal therapy (rituximab in TTP and eculizumab in aHUS) as the mainstay of therapy. Here we discuss the diagnosis and therapy for both disorders.